Analyzing The Impact Of A Teacher’s Teaching Style On Student Learning Motivation Sman 1 Maja - Rafli Imam Muttaqin; Christian Wiradendi Wolor; Darma Rika Swaramarinda (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Abstract This study aims to analyze the impact of teachers’ teaching style on students’ learning motivation at SMAN 1 Maja. This study used qualitative methods with data collection techniques through interviews, observation, and documentation. The research participants consisted of purposively selected X, XI, and XII grade students. The results showed that varied teaching styles, including lectures, group discussions, practical activities, and educational games, had a positive impact on students’ learning motivation. Teachers who were able to create a conducive, interactive and inclusive learning atmosphere succeeded in increasing students’ active participation in learning activities. In addition, the personal closeness between teachers and students also plays an important role in building students’ self-confidence. This study concludes that flexible, creative and adaptive teaching styles can significantly increase students’ learning motivation. Recommendations for this study include the need to develop teacher competence in a variety of teaching methods and improve learning support facilities at school.